Corrosion behavior and lifetime prediction of VM12, Sanicro 25 and Inconel 617 in supercritical carbon dioxide at 600 °C. (October 2020) - Gui, Yong; Liang, Zhiyuan; Shao, Huaishuang; Zhao, Qinxin
Highlights: Corrosion and carburization behavior of VM12, Sanicro 25, and Inconel 617 in supercritical carbon dioxide at 600 °C and 15 MPa was investigated. Chromia-forming alloys Sanicro 25 and Inconel 617 had better corrosion resistance than VM12, which formed Fe-oxide rich scales on its surface. The growth of corrosion layers of the investigated materials followed a parabolic corrosion law. The stability of the Cr2 O3 scale of Sanicro 25 and Inconel 617 was evaluated and the corrosion allowances of the investigated materials were calculated. Abstract: The corrosion behavior of VM12, Sanicro 25, and Inconel 617 in supercritical carbon dioxide at 600 °C and 15 MPa was investigated. Chromia-forming alloys Sanicro 25 and Inconel 617 had better corrosion resistance than VM12, which formed Fe-oxide rich scales on its surface. In all materials, internal carburization zones were found underneath the oxide scales. Based on the results that the growth of corrosion layers of the investigated materials followed a parabolic corrosion law, the stability of the Cr2 O3 scale of Sanicro 25 and Inconel 617 was evaluated and the corrosion allowances of the investigated materials were calculated.